Effect of cooling rate on metallurgical and mechanical properties in continuous wave laser welding of hot-dip galvanised steel-to-aluminium sheets in a zero part-to-part gap lap joint configuration - A. Baghbani Barenji; M.B. Russo; S. Jabar; H.R. Kotadia; D. Ceglarek; K.F. Ayarkwa; J.R. Smith; P. Franciosa (Journal of Advanced Joining Processes)
Using a continuous wave (CW) laser with beam oscillation, this study elucidates the impact of passive and active cooling on welding hot-dip galvanised steel-to-aluminium sheets. The work investigates how cooling affects the formation of intermetallic compounds (IMCs) and the behaviour of Zn vapours, both of which are critical factors to the joint strength. IMCs are recognised as the most decisive factor in welding steel to aluminium, while Zn vapours significantly impact welding in a zero part-to-part gap overlap configuration. A 3D finite element method thermal model was employed to correlate the thermal cycles to the metallurgical and mechanical properties. The cooling rate without beam oscillation increased by 34% switching from passive to active cooling, while it was only 2.5% with oscillation present (2.5 mm lateral oscillation). Results revealed that active cooling influences Zn vapours and IMCs differently; faster cooling reduced total IMCs and Fe2Al5 phase and increased joint strength; however, it exacerbated spattering and weld discontinuity due to insufficient time for outgassing the Zn vapours from the molten pool. This adverse effect was more pronounced with beam oscillation due to larger molten pool. The experimental work also showed that despite beam oscillation does enlarge the connection area, the average shear stress was relatively lower compared to the case without oscillation, attributed to the increased thickness of the IMCs. Active cooling with water flow at 10 °C achieved 60% joint efficiency compared to parent aluminium, while beam oscillation reduced this to 54% but with half the strength variation. This highlights the complex, non-linear interplay between IMC formation, Zn vapour outgassing, and the dynamics of the molten pool.